Mucosal-Associated Invariant T Cells in the Human Gastric Mucosa and Blood: Role in Helicobacter pylori Infection - Booth, Jayaum S.; Salerno-Goncalves, Rosangela; Blanchard, Thomas G.; Patil, Seema A.; Kader, Howard A.; Safta, Anca M.; Morningstar, Lindsay M.; Czinn, Steven J.; Greenwald, Bruce D.; Sztein, Marcelo B. (Frontiers in Immunology, 2015)
Mucosal-associated invariant T (MAIT) cells represent a class of antimicrobial innate-like T cells that have been characterized in human blood, liver, lungs and intestine. Here, we investigated, for the first time, the presence of MAIT cells in the stomach of children, adults and the elderly undergoing routine endoscopy and assessed their reactivity to Helicobacter pylori (H. pylori-Hp), a major gastric pathogen. We observed that MAIT cells are present in the lamina propria compartment of the stomach and display a similar memory phenotype to blood MAIT cells. We then demonstrated that gastric and blood MAIT cells are able to recognize H. pylori. We found that CD8+ and CD4-CD8- (DN) MAIT cell subsets respond to H. pylori-infected macrophages stimulation in a MR-1 restrictive manner by producing cytokines (IFNg, TNFa, IL-17A) and exhibiting cytotoxic activity. Interestingly, we observed that blood MAIT cell frequency in Hp+ve individuals was significantly lower than in Hp-ve individuals. However, gastric MAIT cell frequency was not significantly different between Hp+ve and Hp-ve individuals, demonstrating a dichotomy between blood and gastric tissues. Further, we observed that the majority of gastric MAIT cells (>80%) expressed tissue-resident markers (CD69+ CD103+), which were only marginally present on PBMC MAIT cells (<3%), suggesting that gastric MAIT cells are readily available to respond quickly to pathogens. These results contribute important new information to the understanding of MAIT cells function on peripheral and mucosal tissues and its possible implications in the host response to H. pylori.